Genetic and compositional analysis of biofilm formed by Staphylococcus aureus isolated from food contact surfaces - Avila-Novoa, María Guadalupe; Solis-Velazquez, Oscar Alberto; Guerrero-Medina, Pedro Javier; González-Gómez, Jean-Pierre; González-Torres, Berenice; Velázquez-Suárez, Noemí Yolanda; Martínez-Chávez, Liliana; Martínez-Gonzáles, Nanci Edid; De la Cruz-Color, Lucia; Ibarra-Velázquez, Luz María; Cardona-López, Marco Antonio; Robles-García, Miguel Ángel; et al. (Frontiers in Microbiology, 2022)
Staphylococcus aureus is an important pathogen that can form biofilms on food contact surfaces (FCS) in the dairy industry, posing a serious food safety and quality concern. Biofilm is a complex system, influenced by nutritional-related factors that regulate the synthesis of the components of the biofilm matrix. This study determines the prevalence of biofilm-associated genes and evaluates the development under different growth conditions and compositional of biofilm produced by S. aureus. Biofilms were developed in TSB, TSBG, TSBNaCl, and TSBGNaCl on stainless-steel (SS), with enumeration at 24 and 192 h visualized by epifluorescence and scanning electron microscopy (SEM). The composition of biofilms was determined using enzymatic and chemical treatments and confocal laser scanning microscopy (CLSM). Eighty-four S. aureus (SA1-SA84) strains were collected from 293 dairy industry FCS FCS-stainless steel (n = 183) and FCS-polypropylene (n = 110) of dairy for this study. The isolates harbored the genes sigB (66%), sar (53%), agrD (52%), clfB/clfA (38%), fnbA/fnbB (20%), and bap (9.5%). In particular, the biofilm formed by bap-positive S. aureus onto SS showed a high cell density in in all culture media at 192 h in comparison with the biofilms formed at 24 h (p < 0.05). Epifluorescence microscopy and SEM revealed the metabolically active cells and the different stages of biofilm formation. CLSM analysis detected extracellular polymeric of S. aureus biofilms on SS, such as eDNA, proteins, and polysaccharides. Finally, the level of detachment on being treated with DNase I (44.7%) and NaIO4 (42.4%) was greater in the biofilms developed in TSB compared to culture medium supplemented with NaCl at 24 h, however, there was no significant difference when the culture medium was supplemented with glucose. In addition, after treatment with proteinase K, there was a there was a lower level of biomass detachment (17.7 %) of the biofilm developed in TSBNaCl (p < 0.05 at 24 h) compared to that in TSB, TSBG, and TSBGNaCl (33.6, 36.9 and 37.8 %, respectively). These results represent a deep insight into the composition of S. aureus biofilms present in the dairy industry, which promotes the development of more efficient composition-specific disinfection strategies.